Novel Strategies to Reduce Pulmonary Hypertension in Infants With Bronchopulmonary Dysplasia - Ahmed El-Saie; Binoy Shivanna (Frontiers Media S.A., 2020)
Bronchopulmonary dysplasia (BPD) is a developmental lung disorder of preterm infants primarily caused by the failure of host defense mechanisms to prevent tissue injury and facilitate repair. This disorder is the most common complication of premature birth, and its incidence remains unchanged over the past few decades. Additionally, BPD increases long-term cardiopulmonary and neurodevelopmental morbidities of preterm infants. Pulmonary hypertension (PH) is a common morbidity of BPD. Importantly, the presence of PH increases both the short- and long-term morbidities and mortality in BPD infants. Further, there are no curative therapies for this complex disease. Besides providing an overview of the pathogenesis and diagnosis of PH associated with BPD, we have attempted to comprehensively review and summarize the current literature on the interventions to prevent and/or mitigate BPD and PH in preclinical studies. Our goal was to provide insight into the therapies that have a high translational potential to meaningfully manage BPD patients with PH.